How to Become an Author: The Poet Isa Asp and Her Childhood Fascination with Writing for Magazines - Kotilainen, Sofia (Knygotyra, 2021)
In this article the author explores the early development of the identity as a writer of a Finnish-speaking poet Lovisa (or Isa) Asp (1853–1872). She wrote her lyrics in the Finnish language in the 1870s, and she is regarded as the first 19th-century female Finnish poet (whose works were published in Finnish). She began writing poetry (initially in Swedish) as a teenager and started her literary career as a contributor to children’s magazines. Asp began her studies at the Teacher Training College in Jyväskylä in autumn 1871 with the aim of working as an elementary school teacher, but she also dreamt of becoming an established writer someday. Unfortunately, her early death meant that most of her poetry remained unpublished until the 21st century. The author investigates what kind of literature Asp read and why she was able to read extensively as a child in the remote Finnish-speaking countryside at a time when Finnish-language literature for children was scarce and still only nascent and being developed for nationalistic reasons; in those decades, most of the books and publications were still written in Swedish. The author analyses in particular the gendered experiences of reading (and writing) in the life of a young girl and woman from the countryside, because in those days most of the authors were men living in towns. A special focus of the article is on the texts that she wrote and edited for children’s magazines. The author studies her autobiographical sources using a biographical method and considers what kind of literature and libraries inspired her career as an early female poet. National poet Johan Ludvig Runeberg and poet and historian Zacharias Topelius, the major Fennoman authors, were the literary models for the young Isa Asp. Their works inspired her to write and to aspire for a career as a poet and author, an occupation that was then still rare for a woman. Writing for children’s magazines was a crucial stage in her career, and her identity as a writer was strengthened by the opportunity to have her poems and short tales published. Also, writing for these handwritten as well as published magazines made her dreams visible and encouraged her to pursue them with effort. All this shows that her development as a writer was a deliberate, goal-oriented process. The publication of her poems and obtaining the community’s approval of them were important for the young poet. The encouragement to pursue a career in writing that Isa with her literary gifts received as a child from her immediate surroundings helped her to achieve her dreams, which in the end turned out not to be impossible to realise.